A computer touch screen system and training procedure for use with primate infants: Results from pigtail monkeys (Macaca nemestrina) - Mandell, Dorothy J.; Sackett, Gene P. (Developmental psychobiology, 2008)
Computerized cognitive and perceptual testing has resulted in many advances towards understanding adult brain–behavior relations across a variety of abilities and species. However, there has been little migration of this technology to the assessment of very young primate subjects. We describe a training procedure and software that was developed to teach infant monkeys to interact with a touch screen computer. Eighteen infant pigtail macaques began training at 90‐postnatal days and five began at 180‐postnatal days. All animals were trained to reliably touch a stimulus presented on a computer screen and no significant differences were found between the two age groups. The results demonstrate the feasibility of using computers to assess cognitive and perceptual abilities early in development. © 2008 Wiley Periodicals, Inc. Dev Psychobiol 50: 160–170, 2008.